Modification of the cast structure of stainless steel AISI310s and its influence on mechanical properties - Ozbayraktar, Serdar (My University, 1992)
A close relationship exists between the macrostructure of as-cast alloys and their mechanical properties and extensive research has gone into the modification of as-cast structures in attempts to improve mechanical properties. ( abbreviation abstract)
A thesis submitted to the Faculty of Engineering, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Doctor of Philosophy
Keywords: Stainless steel--RESEARCH.; Stainless steel--THERMAL PROPERTIES.; Stainless steel--COLD WORKING.; Stainless steel--HEAT TREATMENT.; ROLLING (METAL-WORK)--RESEARCH.; STEEL CASTINGS--RESEARCH.